Managing Motorcycle Safety and Youth Riders in Rapidly Growing Indonesian Communities - Dewa, Adenanthera (Economic and Business Horizon, 2023)
Road safety is an effort to reduce traffic accidents and their consequences. When road users follow traffic regulations, road safety levels increase. Road users are expected to prioritize safety when driving on the highway. Numerous factors influence road safety, including environmental conditions, weather, driver behavior, road conditions, vehicle equipment, and the enforcement of traffic laws, all of which significantly affect traffic congestion. In this research, three variables will be analyzed: driver behavior, vehicle equipment, and traffic law enforcement, serving as independent variables that influence road safety, the dependent variable. The problem formulation, research objectives, and hypotheses in this study aim to analyze how independent variables, such as driver behavior, vehicle equipment, and adherence to traffic laws, impact road safety. The study focuses on underage motorcycle users in Tawangsari Village, Wonosobo Regency. Data sources include primary and secondary data. The study's sample consists of 100 respondents who are parents with children in Tawangsari Village, Wonosobo Regency